A Mixed Methods Exploration of Economic Factors Role in Fashion Specialty Retailers’ International Expansion and Performance - Testa, Danielle Sponder; Slaton, Kelcie; Karpova, Elena (Journal of Marketing Development and Competitiveness, 2022)
As globalization swells and businesses find success through expansion into new markets, there continue to be complexities to the factors that motivate retail international expansion. This study considers the modern relevance of economic factors in international expansion, specifically in fashion specialty retail, a continually expanding sector. The purpose of this study was to (1) examine what economic factors of foreign countries motivate fashion specialty retailers to open stores, and (2) analyze how those factors interacted with the brand’s sales performance. Financial and economic data was retrieved and quantitively analyzed. Further, case-study analysis of each retailer provided context to the findings.